2021
DOI: 10.4103/ija.ija_149_21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of using remdesivir in patients with moderate to severe COVID-19

Abstract: Background and Aims: When the world was frantically searching for a drug effective against the coronavirus disease (COVID)-19, remdesivir, a broad-spectrum anti-viral medication, became a part of the COVID treatment. We planned a study to evaluate improvement in clinical outcomes with remdesivir treatment for five days. Methods: Participants more than 40-years old and with moderate to severe COVID-19 but not on mechanical ventilation were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 12 publications
2
80
0
6
Order By: Relevance
“…The WHO's pivotal SOLIDARITY trial (n= 2 743) found that RDV treatment had no real effects on mortality or the course of the disease and did not show overall efficacy [24]. This study, supported by two other smaller studies, including a nor-solidarity trial, provided sufficient evidence to conclude that RDV has little efficacy to offer [22,23]. Some improvement was seen when combining RDV with barcitinab, but this was not convincing [21].…”
Section: Figure 1 Prisma Diagrammentioning
confidence: 80%
See 1 more Smart Citation
“…The WHO's pivotal SOLIDARITY trial (n= 2 743) found that RDV treatment had no real effects on mortality or the course of the disease and did not show overall efficacy [24]. This study, supported by two other smaller studies, including a nor-solidarity trial, provided sufficient evidence to conclude that RDV has little efficacy to offer [22,23]. Some improvement was seen when combining RDV with barcitinab, but this was not convincing [21].…”
Section: Figure 1 Prisma Diagrammentioning
confidence: 80%
“…Eight RCTs, including the WHO's SOLIDARITY trial, involving a total of 4 829 patients, have tested the efficacy of RDV (Table 1). Early studies, [17][18][19][20] showed promising results while later larger trials, [21][22][23][24] disputed these findings. Initial trials indicated that RDV showed potential, most notably in studies conducted by Wang et al and Beigel et al [17,18].…”
Section: Figure 1 Prisma Diagrammentioning
confidence: 99%
“…The RCT has been conducted by The Adaptive COVID-19 Treatment Trial (ACTT) showed shortened duration of disease course and mortality reduction in patients who needed supplemental oxygen [23]. Conversely, another large international, multi-arm, RCT named "Solidarity" [24] and other RCTs [25,26] has not reported an overall reduction in mortality of COVID-19 hospitalized patients who received remdesivir. Overall, Solidarity has not reported mortality benefit, shortened time to discharge or ventilation requirement reduction following the administration of remdesivir.…”
Section: Synthetic Drugsmentioning
confidence: 99%
“…The living, rapid systematic review identified 1 new randomized controlled trial that met inclusion criteria, comparing a 5-day course of remdesivir to standard care in adults hospitalized with COVID-19 not requiring invasive ventilation at baseline (5). The new study, however, was determined to be of poor quality (high risk of bias).…”
Section: Updated Rationalementioning
confidence: 99%
“…This is an update of the American College of Physicians' living, rapid practice points about using remdesivir for treatment of COVID-19 (1), which is based on an updated systematic review done through 10 May 2021 (2)(3)(4). The evidence update identified 1 new study that could inform Practice Point 1 (5). No new studies were identified as supporting evidence for Practice Points 2 or 3.…”
mentioning
confidence: 99%